Case Report: Adrenal glands degenerated schwannoma: Report of three cases and literature review - Zhang, Tao; Yin, Si-fan; Feng, Wen-bo; Feng, Run-lin; Ke, Chang-xing (Frontiers in Oncology, 2023)
Background Schwannoma is a benign tumor, of which degenerated schwannoma is a subtype. Retroperitoneal schwannomas are extremely rare, as they account for only 3% of retroperitoneal tumors.Degenerated schwannoma is a schwannoma subtype. However,degenerated schwannoma occurring in the adrenal glands is extremely rare. Case summary Case 1: A 42-year-old man was referred to our hospital for further examination of a left adrenal mass that was incidentally discovered during a routine physical check-up.No significant abnormalities were found in laboratory tests results. Robotic-assisted laparoscopic excision of the left adrenal gland was performed under general anesthesia. Case 2: A 47-year-old man was admitted to the hospital because of a left adrenal mass found on a routine physical examination.The patient was previously in good health, and there was no family history of a similar disorder. Left-sided laparoscopic adrenalectomy was performed under general anaesthesia. Case 3: A 62-year-old woman with hypertension and diabetes mellitus was referred to our hospital after an incidentally found left adrenal mass.There was no family history of a similar disorder. Left-sided laparoscopic adrenalectomy was performed under general anaesthesia. None of the patients had a recurrence in our study during the postoperative follow-up. Conclusion Degenerated schwannoma of the adrenal glands is very rare. The clinical presentations of degenerated schwannoma are nonspecific; a small number of patients do not have any symptoms, and the mass is only found incidentally during physical examination for any number of reasons. The preoperative diagnosis of adrenal degenerated schwannoma is difficult because the diagnosis must rely on pathological examination and immunohistochemistry assays. The management is surgical excision and regular follow-up.